FREQUENCY-CURRENT INVARIANT ELECTRIC DRIVE ON THE BASIS OF ACTIVE CONVERTERS - V. I. Lukovnikov; V. V. Logvin; A. I. Rozhkov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper presents two systems of vector asynchronous electric drives that are invariant to an oscillatory load moment. Conclusions of the paper prove an advantage of the second system in comparison with the first one.